Fragments of modernity, shadows of the gothic : questions of representation and perception in William Kentridge's "I am not me, the horse is not mine" (2008) - Stuart-Clark, Lucy Bena (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2012.